Financial sector development and macroeconomic volatility: Case of the Southern African Development Community region - Kapingura Forget Mingiri; Nwabisa Mkosana; Suhal Kusairi (Cogent Economics & Finance, 2022)
The study examines the effect of financial sector development on macroeconomic volatility in the Southern African Development Community (SADC) region for the period 1980-2018 employing the Cross-Sectionally Augmented Autoregressive Distributed Lag (CS-ARDL) model. The empirical findings show that banking variables have a negative and significant effect on growth volatility in the SADC countries. Also, stock market capitalisation, which is a measure of capital market development, was also found to have a negative effect on macroeconomic volatility when looking at the whole financial sector. The results suggest that a well-developed capital market where both the stock market and banking sector are thriving mitigates macroeconomic volatility. The empirical results however reveal that when the stock market is dominant, there is bound to be macroeconomic volatility. The results imply that pursuing the development of the overall financial system reduces macroeconomic volatility in a country as well as the region. Authorities should therefore ensure that policies geared towards development of the entire financial system are pursued.
Keywords: 330; Macroeconomics; Financial sector development; CS-ARDL; SADC